Urinary ATP may be a dynamic biomarker of detrusor overactivity in women with overactive bladder syndrome - Silva-Ramos, M. (2014)
Background Nowadays, there is a considerable bulk of evidence showing that ATP has a prominent role in the regulation of human urinary bladder function and in the pathophysiology of detrusor overactivity. ATP mediates nonadrenergic-noncholinergic detrusor contractions in overactive bladders. In vitro studies have demonstrated that uroepithelial cells and cholinergic nerves from overactive human bladder samples (OAB) release more ATP than controls. Here, we compared the urinary ATP concentration in samples collected non-invasively from OAB women with detrusor overactivity and age-matched controls. Methods Patients with neurologic diseases, history of malignancy, urinary tract infections or renal impairment (creatinine clearance <70 ml/min) were excluded. All patients completed a 3-day voiding diary, a 24 h urine collection and blood sampling to evaluate creatinine clearance. Urine samples collected during voluntary voids were immediately freeze-preserved for ATP determination by the luciferin-luciferase bioluminescence assay; for comparison purposes, samples were also tested for urinary nerve growth factor (NGF) by ELISA. Results The urinary content of ATP, but not of NGF, normalized to patients’ urine creatinine levels (ATP/Cr) or urinary volume (ATP.Vol) were significantly (P<0.05) higher in OAB women with detrusor overactivity (n = 34) than in healthy controls (n = 30). Significant differences between the two groups were still observed by boosting urinary ATP/Cr content after water intake, but these were not detected for NGF/Cr. In OAB patients, urinary ATP/Cr levels correlated inversely with mean voided volumes determined in a 3-day voiding diary. Conclusion A high area under the receiver operator characteristics (ROC) curve (0.741; 95% CI 0.62–0.86; P<0.001) is consistent with urinary ATP/Cr being a highly sensitive dynamic biomarker for assessing detrusor overactivity in women with OAB syndrome.